The Physiological and Ergogenic Effects of Khat (Catha edulis Forsk) Extract. (2nd January 2018) - Sallam, Mowaffaq Awad; Sheikh, Kamaludin Ahmed; Baxendale, Ronald; Azam, Mohammad Nurul; Hossain, Anwar M.; El-Setouhy, Maged
ABSTRACT: Background: Khat ( Catha edulis Forsk) is a natural psychoactive substance which contains two main addictive substances; Cathine and Cathinone. Khat is widely used in east Africa and southern Arabian Peninsula. Khat chewers believe that it improves work capacity and increases energy level and alertness. That is why we aimed in this study to investigate the physiological and ergogenic effects of khat extract. Methods: This study is an experimental study conducted at the Substance Abuse Research Centre in Jazan University, Saudi Arabia. Thirty healthy young volunteers were randomly assigned into two experimental groups. The first group ingested 45 g of grounded khat leaves extract mixed with juice in the first session then placebo (juice only) in the second session. While the second group ingested the placebo in the first session and the grounded khat leaves with juice in the second session. Experiments were done between December 2012 and March 2013. We recorded the blood pressure, heart rate, grip strength, and reaction time every 15 min for 75 min after each ingestion. The study proposal was reviewed and approved by Research Ethics Committee (REC) of the Medical Research Centre in Jazan University. Results: The results showed the consumption of 45 g of grounded khat leaves contributed to the increase in blood pressure (SBP & DBP) and reaction time ( p < 0.05); but had no significant effect on heart rate and grip strength ( p > 0.05). Conclusions: The findings of this study showed that Khat has an acute effect on some physiological parameters. These findings support the prohibition of cathinone and cathine by the World Anti-Doping Agency (WADA, 2016).